STRATEGI PEMBELAJARAN MAHARAH KALAM PERSPEKTIF PENDEKATAN KOMUNIKATIF DI PONDOK PESANTREN DARUL LUGHAH WADDIRASAT AL-ISLAMIYAH PAMEKASAN - Thia Razimona (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2022)
The purpose of language teaching is to obtain communicative skills with language effectively. In the process of learning the strategy has an important role in achieving the learning objectives. Learning strategies are one of the ways that teachers use in delivering learning material. Choosing the right strategy will facilitate the achievement of the expected learning goals.The purpose of this study was to analyze (1) learning strategies the speaking skills of perspective communicative approach of the students of Darul Lughoh Waddirasat Al Islamiyah Islamic Boarding School Pamekasan Madura, and to find out the advantages and disadvantages of the learning strategies of speaking skills in the communicative approach of Darul Lughoh Waddirasat Al Islamiyah Pamekasan Islamic Boarding School Madura.This research is a field research in the form of qualitative descriptive research about Learning Strategies The Speaking Skills Perspective Communicative Approach Students of Islamic Boarding School Darul Lughoh Waddirasat Al Islamiyah Pamekasan Madura. Data collection is done by interview, observation, and documentation techniques. Data techniques analysis include data reduction, data display, and conclusion drawing/ verifying. Checking the validity of data through triangulation technique. The results of this study are four types of strategies used in learning speaking skills perspective communicative approach of Islamic Boarding School Darul Lughoh Waddirasat Al Islamiyah Pamekasan Madura: 1) Direct Strategy 2) Strategy viewing images 3) Demonstration Strategy, and 4) Discussion Strategy Keywords: Learning Strategie, Communicative Skills, Communicative Approaches